Silicone plastination of a whole dissected body - Ezhilarasan, Ezhilarasan; Jeyanthi, Jeyanthi (International Journal of Medical Research and Review, 2016)
Plastination is a technique developed by Von Hagans in the year 1979. In this technique water and lipids present inside the tissue are replaced by a curable polymer, resulting in a dry odorless specimen that can be kept without any change for years together. Water and lipids present in the tissues cannot, however, be replaced directly with the polymer, because the two are chemically incompatible. So initially the water and lipids are replaced by a dehydrating agent like acetone and this dehydrating agent is subsequently replaced by the curable polymer by applying vacuum. The polymer is subsequently hardened, resulting in a dry, odorless specimen. Whole body silicone plastination is done in many institutions of Anatomy in foreign countries. In India plastination of whole dissected bodies using silicone polymer is not practiced until now. In our present study we have plastinated a whole dissected body using a commercially available two component silicone polymer(figure-1) called TSE3455T (A) and a curing agent TSE3455T (B), resulting in a dry odorless dissected whole body specimen, which can be kept in the museum for ready demonstration of the various structures to the medical and paramedical students.